Determinants of allergic signs and symptoms in 24- 48-month-old Turkish children - Ozmert, Elif N; Kale-Cekinmez, Eren; Yurdakök, Kadriye; Sekerel, Bülent Enis (The Turkish Journal of Pediatrics, 2009)
The expression of asthma and allergic diseases depends upon an interaction of genetic and environmental factors and thus may differ between populations. This study was performed to document the factors determining allergic signs and symptoms in early childhood in a group of Turkish children. Children followed at the Well-Baby Clinic who were 2 to 4 years were invited and re-evaluated. In addition to face-to-face questionnaire for allergic signs and symptoms and review of files, skin prick test was performed. The associations between risk factors and different aspects of atopy were analyzed. One hundred and nine patients (mean age: 31.6 +/- 3.5 months) were included in the study. All had been breast-fed with mean exclusive and total breastfeeding durations of 3.3 +/- 2.7 and 13.3 +/- 7.2 months, respectively. Eight children had physician-diagnosed allergic diseases (4 atopic eczema, 3 bronchial asthma and 1 food allergy) and the overall prevalence of sensitization was 13%. Introduction of cow’s milk before 12 months appeared to be a significant risk factor for atopy. Smoking during lactation and having an older sibling showed a trend towards an increase while regular yoghurt consumption showed a trend to decrease the risk for atopy. No significant risk factor could be defined for ever wheezing. It was concluded that in young Turkish children, early introduction of cow’s milk, passive smoking and having an older sibling may predict atopy whereas regular yoghurt consumption may decrease the risk of atopy. These results also support the concept that variability may exist between populations.